Rancang Bangun Alat Uji Tarik Serat Alam - Muhammad Arsyad; Jeremiah Ritto; Abdul Rachman; Dewi Rachma Ayu Lestari; Edyson Palembangan (Jurnal Teknik Mesin Sinergi, 2019)
The aim of this research are to design and to make natural fiber tensile strength test as well as to recognize the characteristics of natural fiber. The specimen testing is done using ASTM 3379-02 standard. The methods that we used are designing, making, assembling and testing. This equipment is designed simply by using water as a load. When used, the water continues to be flowed to the reservoir which is connected in such a way that the fiber breaks. When the fiber breaks, the mass of water is weighed as a burden which causes the fiber to break. Tensile strength of the results of testing equipment is 282.35 N/mm2 compared with the tensile strength of the results of the tensile test equipment at UNM 186.42 N/mm2 and the value of the tensile strength of the literature 284.08 N/mm2. The value obtained is between the tensile strength of the results of the UNM tensile test equipment with the tensile strength of the literature. According to these results it was concluded that the tensile test equipment made can be used to determine the tensile strength of natural fibers, one of which is coconut fiber. The natural fiber tensile test equipment can be used to determine the tensile strains of coconut fiber.